2017
DOI: 10.18553/jmcp.2017.16272
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Patient Support Program on Patient Adherence to Adalimumab and Direct Medical Costs in Crohn’s Disease, Ulcerative Colitis, Rheumatoid Arthritis, Psoriasis, Psoriatic Arthritis, and Ankylosing Spondylitis

Abstract: Design, study conduct, and financial support for this study were provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. All authors contributed to the development of the publication and maintained control over the final content. Rubin has received consulting fees or research support from AbbVie, Amgen, Emmi, Genentech, Ironwood, Janssen, Pfizer, Prometheus, Shire, and Takeda. Skup and Mittal are employees and stockholders of AbbVie. Chao was an employee of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 27 publications
2
76
0
Order By: Relevance
“…However, a trend toward more stringent adherence to topical therapies and lower reported adverse effects was noted in the interventional group. MPCs may thus become a relevant component of integrated protocols that utilize other potentially beneficial adherence-enhancing strategies (Alinia et al, 2017;Balato, Megna, Di Costanzo, Balato, & Ayala, 2013;Feldman et al, 2017;Hawkins, Barilla, & Feldman, 2017;Hong, Papp, Lophaven, Skallerup, & Philipp, 2017;Reich, Mrowietz, Karakasili, & Zschocke, 2014;Reich et al, 2017;Rubin et al, 2017), such as textmessage reminders. MPC = motivational phone call; visit 1 = first appointment, at time of enrollment; visit 2 = second appointment, at time of conclusion (6 AE 1 months after enrollment).…”
Section: Discussionmentioning
confidence: 99%
“…However, a trend toward more stringent adherence to topical therapies and lower reported adverse effects was noted in the interventional group. MPCs may thus become a relevant component of integrated protocols that utilize other potentially beneficial adherence-enhancing strategies (Alinia et al, 2017;Balato, Megna, Di Costanzo, Balato, & Ayala, 2013;Feldman et al, 2017;Hawkins, Barilla, & Feldman, 2017;Hong, Papp, Lophaven, Skallerup, & Philipp, 2017;Reich, Mrowietz, Karakasili, & Zschocke, 2014;Reich et al, 2017;Rubin et al, 2017), such as textmessage reminders. MPC = motivational phone call; visit 1 = first appointment, at time of enrollment; visit 2 = second appointment, at time of conclusion (6 AE 1 months after enrollment).…”
Section: Discussionmentioning
confidence: 99%
“…Participation in the PSP has been associated with significantly reduced total cost, all-cause medical cost, and disease-related medical cost in patients with Crohn's disease, ulcerative colitis, rheumatoid arthritis, psoriasis, psoriatic arthritis, and AS treated with ADA [11]. However, a formal economic evaluation was not within the scope of the current study, and real-world studies in the future can focus on examining the economic impact of PSP strategies, specifically in patients with AS treated with ADA.…”
Section: Not Controlled Referencementioning
confidence: 99%
“…Both short-term and long-term clinical studies have demonstrated the efficacy and safety of TNF antagonists in patients with AS [10]. However, poor persistence with and non-adherence to treatment with biologics can undermine the effectiveness of these medications [11,12]. Considering the high rates ([ 40%) of non-adherence observed with chronic TNF antagonist treatment [12], it is necessary to explore approaches to improve patient adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Background: The diagnosis of rheumatoid arthritis (RA) using EULAR criteria through conventional assessments remains controversial, especially for those with seronegative results, many of patients without other diagnostic aids as imaging, could be wrong diagnosed followed by expensive treatments (1)(2)(3). Objectives: To evidence through real-world data how the use of imaging within a screening process of diagnosis of RA can saving future costs for unnecessary treatments in patients with misdiagnosis of RA.…”
mentioning
confidence: 99%